2014
DOI: 10.1016/j.bcp.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Nur77 by hyperoside inhibits vascular smooth muscle cell proliferation and neointimal formation

Abstract: Nur77 is an orphan nuclear receptor that belongs to the nuclear receptor 4A (NR4A) subfamily, which has been implicated in a variety of biological events, such as cell apoptosis, proliferation, inflammation, and metabolism. Activation of Nur77 has recently been shown to be beneficial for the treatment of cardiovascular and metabolic diseases. The purpose of this study is to identify novel natural Nur77 activators and investigate their roles in preventing vascular diseases. By measuring Nur77 expression using q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…Hyperoside is a major bioactive compound in P. vulgaris spicas (Kim et al 2014) and exhibits a variety of biological activities, such as anticancer, anti-inflammatory, antioxidant and cardiovascular protective effects (Choi et al 2011;Kim et al 2011;Huo et al 2014;Liu et al 2016). In this study, UV-B radiation increased hyperoside accumulation in P. vulgaris spicas.…”
Section: Antioxidant System Control Uv-bmentioning
confidence: 64%
“…Hyperoside is a major bioactive compound in P. vulgaris spicas (Kim et al 2014) and exhibits a variety of biological activities, such as anticancer, anti-inflammatory, antioxidant and cardiovascular protective effects (Choi et al 2011;Kim et al 2011;Huo et al 2014;Liu et al 2016). In this study, UV-B radiation increased hyperoside accumulation in P. vulgaris spicas.…”
Section: Antioxidant System Control Uv-bmentioning
confidence: 64%
“…This hypothesized pathway was supported by modern researches, some ingredients of FLCWK regulated smooth muscle by similar mechanisms, such as rutin and quercetin inhibiting the smooth muscle via the NO signaling pathways. [46][47][48][49][50] Similarly, K + channels also play a major role in the curative mechanism of FLCWK for IBS-D. The diversity of K + channels described in GI smooth muscles mainly includes voltage-gated K + channels, K A channels, calcium-activated K + channels, and ATPsensitive K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that hyperoside protects cardiomyocytes from oxidative stress caused by ischemia and perfusion through significant upregulation of extracellular signal-regulated protein kinase (ERK) [36]. Hyperoside inhibited vascular lesions produced in a carotid artery ligation rat model [37]. It also possesses anticoagulant effects, as demonstrated through its capacity to restrain the production of thrombin and activated factor X (FXa), and extension of activated partial thromboplastin time (aPTT) and prothrombin time (PT) as well as inhibition of thrombin and FXa in HUVECs [13].…”
Section: Cardiovascular Protective Activitymentioning
confidence: 97%